PERANCANGAN SISTEM MANAJEMEN PERSEDIAAN BARANG MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) PADA CV. CAHAYA MITRA PRATAMA: PERANCANGAN SISTEM MANAJEMEN PERSEDIAAN BARANG MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) PADA CV. CAHAYA MITRA PRATAMA - Zheika Saptoni; Maryam (LPPM Universitas Abdurrab, 2026)
Effective inventory control is a crucial element in a company's logistics operations to achieve financial efficiency. CV. Cahaya Mitra Pratama currently relies on manual recording alongside an existing historical system, resulting in two main problems: double-entry redundancy that risks stock data discrepancies, and the absence of an optimal ordering analysis mechanism that leads to overstock and stockout risks. This research aims to design and develop a web-based Inventory Management System implementing the Economic Order Quantity (EOQ), Safety Stock, and Reorder Point (ROP) methods using the Laravel framework and MySQL database. Calculation validation was conducted through a comparative analysis between the company's conventional inventory policy and the EOQ model calculations. Black Box Testing of system functionality showed Valid results across all 15 test scenarios, while System Usability Scale (SUS) testing involving 30 respondents yielded an average score of 72.83, categorized as Acceptable with Grade Scale B (Good). The developed system successfully eliminated recording redundancy and produced more efficient ordering recommendations compared to the conventional policy.